2014
DOI: 10.1631/jzus.b1400005
|View full text |Cite
|
Sign up to set email alerts
|

Inverse associations of outdoor activity and vitamin D intake with the risk of Parkinson’s disease

Abstract: Abstract:Early studies had suggested that vitamin D intake was inversely associated with neurodegenerative diseases, such as Alzheimer's disease and multiple sclerosis. However, the associations of vitamin D intake and outdoor activities with Parkinson's disease (PD) are still unclear, so this study is to evaluate these relationships from a case-control study in elderly Chinese. The study population involved 209 cases with new onsets of PD and 210 controls without neurodegenerative diseases. The data on dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Following full text assessment 28 references were then excluded for being mechanistic studies or not providing enough data. Finally, seven eligible studies comprising 5690 PD patients and 21251 matched controls were identified, which formed the basis of the present analysis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The seven studies are all observational studies and the years of publication ranged from 2008 to 2015.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following full text assessment 28 references were then excluded for being mechanistic studies or not providing enough data. Finally, seven eligible studies comprising 5690 PD patients and 21251 matched controls were identified, which formed the basis of the present analysis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The seven studies are all observational studies and the years of publication ranged from 2008 to 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Two case-control studies covering 458 patients with PD and 578 cases were included in the assessment of association between vitamin D supplementation and PD risk and the main descriptive data from the studies are shown in Table 2 [ 18 , 19 ]. As shown in Figure 3 , the calculated OR for comparison of the highest with the lowest vitamin D supplementation was 0.62, 95% CI 0.35 to 0.90.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown a strong correlation between motor dysfunction and vitamin D shortage (outdoor activity and total vitamin D intake are inversely associated with PD [19] but no conclusive evidences link cognitive dysfunctions and low vitamin D levels. A cross-sectional and longitudinal case-control study of 388 patients (mean Hoehn and Yahr stage of 2.1 ± 0.6) and 283 control subjects showed an increased frequency of vitamin D deficiency in PD patients compared to controls and a correlation of low 25(OH)D levels with higher total Unified Parkinson's Disease rating Scale (UPDRS) scores at baseline and during follow up [20].…”
Section: Introductionmentioning
confidence: 97%
“…Parkinson’s disease (PD) is a common progressive neurodegenerative disorder mostly occurring in elderly humans. Although the pathogenesis of PD is unclear, environmental factors, including some vitamins, have been suggested to be linked with the development of PD [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, vitamin D was considered to be only related to bone metabolism, osteoporosis, and falling. However, vitamin D has recently emerged as a critical factor in the pathogenesis of chronic diseases and progressive neurodegenerative disorders [ 5 , 7 , 8 ]. Additionally, inadequate amounts of vitamin D may play a role in the development of PD [ 9 ], as the loss of dopaminergic neurons in the brain of PD patients could be related to a condition of continuously inadequate vitamin D [ 7 ].…”
Section: Introductionmentioning
confidence: 99%